Effectiveness of Puzzle Therapy as Brain Exercise in Improving Memory Function Among Older Adults with Dementia: A Case Series Study - Ni Komang Matalia Gandari; Ni Luh Putu Apriliani; I Putu Wira Kusuma Putra; I Made Rismawan (Bali Medical and Wellness Journal, 2025)
Background: Memory impairment significantly impacts the quality of life for older adults living with dementia. Non-pharmacological interventions, such as puzzle therapy, have emerged as promising, low-cost strategies for managing cognitive decline and providing environmental enrichment. Objective: To analyze the effectiveness of puzzle therapy as a brain exercise in improving memory function among older adults with moderate dementia. Methods: This case series involved three older adults (aged 74–84 years) residing at the Tresna Werdha Wana Seraya Social Institution in Bali. Participants engaged in puzzle therapy sessions lasting 10–15 minutes, conducted thrice over one week. Cognitive and memory functions were assessed using the Mini-Mental State Examination (MMSE) before and after the intervention. Results: All participants demonstrated measurable cognitive gains. Baseline MMSE scores ranging from 15 to 16 improved to post-intervention scores of 19 to 21, reflecting a consistent mean improvement of 4.0 points. Notable enhancements were observed specifically in the domains of orientation, immediate recall, and concentration. Conclusion: Puzzle therapy serves as a feasible and effective cognitive stimulation tool for improving memory function in older adults with moderate dementia. These findings support the integration of structured brain exercises into routine geriatric nursing care within institutional settings.